Incidental Papillary Thyroid Micro Carcinomas in Patients Undergone for Thyroidectomy (Medical Forum Monthly, 2024)
Objective: The present study aims to ponder at incidence of incidental papillary thyroid microcarcinomas along with clinopathological features of the tumors.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Pathology and Surgery, Jinnah Medical College and Jinnah Teaching Hospital Peshawar from July 2016 to December 2017.Materials and Methods: The research was performed on 1000 patients who were operated for thyroidectomy during one and a half year. For routine histopathological examination H&E stain was used while to stain tumor cells Immunohistochemical markers were used. All the slides were evaluated for papillary thyroid microcarcinomas.Results: Out of 1000 patients, 186 (18.6%) were found with a malignancy. Among these, 6 (3.22%) were found with follicular carcinoma, 5 (2.68%) with lymphoma, 4 (2.15%) with anaplastic carcinoma, 4 (2.15%) with medullary carcinoma, 2(1.07%) with poorly differentiated carcinoma and 165 (88.70%) with papillary carcinoma. Incidental papillary thyroid microcarcinoma (IPTM) was present in 40 cases. In all the cases, total thyroidectomies were performed. Metastasis and relapse were not detected in any of the cases. Histopathological examination is necessary for thyroidectomy specimens as IPTM may escape fine needle aspiration cytology. As multifocality and bilateriality are quite high in IPTM, total thyroidectomies are best to be performed.Conclusion: To diagnose papillary thyroid microcarcinoma, we could not depend FNAC alone rather detailed histopathological assessment is necessary.